Critical interlayers and interfaces in ceramic armour systems - Powell, Dan (Cranfield University, 2024)
Poster contribution to the Defence and Security Doctoral Symposium 2023
Keywords: Ceramic armour; interlayers; Interfaces; wave propagation; ballistic impact; DSDS23; DSDS23 Poster